2010
DOI: 10.1111/j.1600-065x.2010.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Intertwined pathways of programmed cell death in immunity

Abstract: Programmed cell death (PCD) occurs widely in species from every kingdom of life. It has been shown to be an integral aspect of development in multicellular organisms, and it is an essential component of the immune response to infectious agents. An analysis of the phylogenetic origin of PCD now shows that it evolved independently several times, and it is fundamental to basic cellular physiology. Undoubtedly, PCD pervades all life at every scale of analysis. These considerations provide a backdrop for understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 195 publications
(224 reference statements)
0
44
1
Order By: Relevance
“…c-FLIP is a direct inhibitor of caspase-8, whereas caspase-8 is known to transmit activation signals (39,40). Additionally, TLR3, TLR4, and dectin-1 have been shown to trigger IL-1b production in the caspase-8-dependent pathway (41,42).…”
Section: The Suppressive Activity Of C-flip Is Caspase-8-independentmentioning
confidence: 99%
“…c-FLIP is a direct inhibitor of caspase-8, whereas caspase-8 is known to transmit activation signals (39,40). Additionally, TLR3, TLR4, and dectin-1 have been shown to trigger IL-1b production in the caspase-8-dependent pathway (41,42).…”
Section: The Suppressive Activity Of C-flip Is Caspase-8-independentmentioning
confidence: 99%
“…19 Among the various roles of PCD in maintaining the homeostasis of living organisms is its involvement in the advancement of immune responses. [20][21][22] In fact, the development of adaptive and innate immune responses depends on strict regulation of PCD signaling pathways, which are crucial for shaping and maintaining the immune system and ensuring functional immune responses. [20][21][22] For example, PCD is involved in clonal deletion of lymphocytes during an infection, whereas the misregulation of PCD is known to lead to the defective clearance of autoreactive T cells and autoimmune disease.…”
mentioning
confidence: 99%
“…[20][21][22] In fact, the development of adaptive and innate immune responses depends on strict regulation of PCD signaling pathways, which are crucial for shaping and maintaining the immune system and ensuring functional immune responses. [20][21][22] For example, PCD is involved in clonal deletion of lymphocytes during an infection, whereas the misregulation of PCD is known to lead to the defective clearance of autoreactive T cells and autoimmune disease. 23 Figure 1 represents some major events taking place within a cell undergoing apoptosis, or autophagy, or necroptosis and clearly shows that these three types of PCD are heavily interlinked.…”
mentioning
confidence: 99%
“…The mechanisms of PCD in animals have been widely investigated and well documented (Hedrick, Ch'en, & Alves, 2010), whereas little is acquired about the control of plant PCD. Over the past decade, reports found that early calcium flux, mitochondrial release of apoptogenic proteins (such as cytochrome c), activation of caspase-like proteases or metacaspases, are key factors in the utmost destruction of the plant cell (Reape & McCabe, 2010).…”
Section: Introductionmentioning
confidence: 99%